2019
DOI: 10.1063/1.5123149
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Si doping in plasma assisted MBE growth of β-Ga2O3

Abstract: We report on the origin of high Si flux observed during the use of Si as a doping source in plasma assisted MBE growth of -Ga2O3. We show on the basis of secondary ion mass spectroscopy (SIMS) analysis that Si flux is not limited by the vapor pressure of Si but by the formation of volatile SiO. The low sublimation energy of SiO leads to weak dependence of the SiO flux of Si cell temperature and a strong dependence on the background oxygen pressure. Extended exposure to activated oxygen results in reduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 30 publications
2
46
0
Order By: Relevance
“…desorption and oxidization processes. Intentional n-type doping has been demonstrated by using Si, Sn, and Ge as donor dopants [41][42][43][44]. However, it is difficult to control a low doping density on the order of 10 16 cm −3 or less, because the surface of the dopant source in an effusion cell is easily oxidized during the MBE growth by background O species, resulting in the dopant flux hardly controlled.…”
Section: Melt Bulk Growthmentioning
confidence: 99%
“…desorption and oxidization processes. Intentional n-type doping has been demonstrated by using Si, Sn, and Ge as donor dopants [41][42][43][44]. However, it is difficult to control a low doping density on the order of 10 16 cm −3 or less, because the surface of the dopant source in an effusion cell is easily oxidized during the MBE growth by background O species, resulting in the dopant flux hardly controlled.…”
Section: Melt Bulk Growthmentioning
confidence: 99%
“…[1][2][3][4] Recently, β-(Al x Ga 1-x ) 2 O 3 /β-Ga 2 O 3 modulation-doped field-effect transistors (MODFETs) have become an emerging technology for high-power and high-frequency device applications because of the demonstration of a 2D electron gas (2DEG) channel with mobility as high as 180 cm 2 Vs À1 at their heterointerface. [2,[4][5][6][7][8] Demonstration of 2DEG formation in these heterostructures showed that the mobility in β-Ga 2 O 3 -based devices can be higher than the reported mobility range for β-Ga 2 O 3 -based MOSFETs and MESFETs, which are in the range of 50-90 cm 2 Vs À1 . [5,6] In δ-doped β-(Al x Ga 1-x ) 2 O 3 /β-Ga 2 O 3 heterostructures, the band offset in the conduction band energy between β-(Al x Ga 1-x ) 2 O 3 and β-Ga 2 O 3 causes carrier confinement of the electrons in the channel located at the heterointerface, which results in higher mobility.…”
Section: Introductionmentioning
confidence: 79%
“…[2,[4][5][6][7][8] Demonstration of 2DEG formation in these heterostructures showed that the mobility in β-Ga 2 O 3 -based devices can be higher than the reported mobility range for β-Ga 2 O 3 -based MOSFETs and MESFETs, which are in the range of 50-90 cm 2 Vs À1 . [5,6] In δ-doped β-(Al x Ga 1-x ) 2 O 3 /β-Ga 2 O 3 heterostructures, the band offset in the conduction band energy between β-(Al x Ga 1-x ) 2 O 3 and β-Ga 2 O 3 causes carrier confinement of the electrons in the channel located at the heterointerface, which results in higher mobility. [5,6] In an early study on β-(Al x Ga 1-x ) 2 O 3 / Ga 2 O 3 heterostructure-based FETs, a 2DEG channel with a sheet carrier density of 3 Â 10 12 cm À2 was obtained at the interface of the heterojunction, which resulted from a Si-δ doping layer separated by a thin spacer layer from the heterojunction interface.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Growth of β-Ga2O3 has been realized using a variety of techniques such as MBE (Molecular beam epitaxy) 21 , MOCVD (Metal-organic chemical vapor deposition) [5][6][7]22,23 , HVPE (Hydride vapor phase epitaxy) 4,24 , PLD (Pulsed laser deposition) 25 and LPCVD (Low-pressure chemical vapor deposition) [26][27][28][29] . Growth of β-Ga2O3 has already been studied using MBE for a variety of film orientations (010), (-201), ( 001) and (110) and dopants(Si, Sn and Ge) [30][31][32][33][34] . A variety of lateral FETs have been fabricated using MBE-grown β-Ga2O3 films 2,18 .…”
Section: Introductionmentioning
confidence: 99%